Nebulization and In Vitro Upper Airway Deposition of Liposomal Carrier Systems - Mišík, Ondrej; Kejíková, Jana; Cejpek, Ondřej; Malý, Milan; Jugl, Adam; Bělka, Miloslav; Mravec, Filip; Lízal, František (Molecular pharmaceutics, 2024)
Liposomal carrier systems have emerged as a promising technology for pulmonary drug delivery. This study focuses on two selected liposomal systems, namely, dipalmitoylphosphatidylcholine stabilized by phosphatidic acid and cholesterol (DPPC-PA-Chol) and dipalmitoylphosphatidylcholine stabilized by polyethylene glycol and cholesterol (DPPC-PEG-Chol). First, the research investigates the stability of these liposomal systems during the atomization process using different kinds of nebulizers (air-jet, vibrating mesh, and ultrasonic). The study further explores the aerodynamic particle size distribution of the aerosol generated by the nebulizers. The nebulizer that demonstrated optimal stability and particle size was selected for more detailed investigation, including Andersen cascade impactor measurements, an assessment of the influence of flow rate and breathing profiles on aerosol particle size, and an in vitro deposition study on a realistic replica of the upper airways. The most suitable combination of a nebulizer and liposomal system was DPPC-PA-Chol nebulized by a Pari LC Sprint Star in terms of stability and particle size. The influence of the inspiration flow rate on the particle size was not very strong but was not negligible either (decrease of Dv50 by 1.34 μm with the flow rate increase from 8 to 60 L/min). A similar effect was observed for realistic transient inhalation. According to the in vitro deposition measurement, approximately 90% and 70% of the aerosol penetrated downstream of the trachea using the stationary flow rate and the realistic breathing profile, respectively. These data provide an image of the potential applicability of liposomal carrier systems for nebulizer therapy. Regional lung drug deposition is patient-specific; therefore, deposition results might vary for different airway geometries. However, deposition measurement with realistic boundary conditions (airway geometry, breathing profile) brings a more realistic image of the drug delivery by the selected technology. Our results show how much data from cascade impactor testing or estimates from the fine fraction concept differ from those of a more realistic case.
Keywords: Cholesterol; Humans; Administration, Inhalation; cholesterol; 1,2-dipalmitoylfosfatidylcholin; Trachea; deposition; particle size; aerosoly; pulmonary drug delivery; Equipment Design; nebulizer; Liposomes; Bronchodilator Agents; Drug Delivery Systems; lidé; inhalation; nebulizátory a vaporizátory; liposome; Aerosols; velikost částic; trachea; lékové transportní systémy; design vybavení; liposomy; aplikace inhalační; aerosol; Particle Size; 1,2-Dipalmitoylphosphatidylcholine; bronchodilatancia; Nebulizers and Vaporizers